In Vitro Germination, Micropropagation and Addressing the Hyperhydricity of the Balkan Native Dianthus cruentus, a Plant with High Ornamental and Xeriscaping Potential - Apostolos-Emmanouil Bazanis; Maria Papafotiou (Horticulturae, 2024)
Dianthus cruentus Griseb. (Caryophyllaceae) is an herbaceous perennial native to Greece with a strong ornamental potential when used as a pollinator-friendly component of xeric gardens and green roofs, where it is valued for its tolerance of poor, dry soils, and its showy colorful inflorescences. Aiming to develop an efficient mass propagation protocol appropriate for the introduction of the species as a novel floricultural crop, the in vitro seed and clonal propagation of a Greek native xeric ecotype were investigated in this paper for the first time. A total of 90–100% of the seeds, after being stored in the dark at room temperature for 12 months, germinated when incubated at 10 to 25 °C after their surface sterilization and transfer in vitro. Sixty-day-old seedlings grown in vitro were then used as a source of nodal explants for the initial establishment of micropropagation cultures, more efficiently on MS medium with 0.1 mg L−1 6-benzylaminopurine (BA). In the multiplication stage, either normal or hyperhydric micro-shoots were used as explant sources, assessing the possibility of incorporating usually discarded material in the propagation procedure. Different solid media were tested, with the highest multiplication indices (5.1) recorded in an MS medium containing 0.1 mg L−1 BA and 0.05 mg L−1 NAA, regardless of explants’ hyperhydricity, while an MS medium containing 0.1 mg L−1 BA and 12 g L−1 agar proved optimal for the effective reversal of hyperhydric explants (MI: 5.2). Despite higher hyperhydricity and reaction rates being observed when hyperhydric explants were used, modifications in the multiplication medium proved to be highly effective in controlling hyperhydricity, with the highest number of normal shoots (2.4–2.6) produced in BA-containing media. Micro-shoots rooted readily in ½ MS medium (60–100%), with rooting rates and quality positively affected by the presence of 0.5 mg L−1 IBA in the rooting medium and the absence of cytokinins in the multiplication one. Rooted micro-shoots were successfully acclimatized ex vitro at high rates (65–100%), their origin influencing their acclimatization and morphology. Thus, the concurrent use of normal and hyperhydric shoots in the proposed micropropagation protocol is proven to be both feasible and desirable, as it is able to significantly increase efficiency and facilitate the sustainable exploitation and dissemination of D. cruentus as a promising multivalent horticultural crop.